THE ADDRESS TERMS IN ENGLISH AND SELAYERESE: A SOCIOLINGUISTIC PERSPECTIVE - Zavitri, Irma; Machmoed, Hamzah; Sukmawaty, Sukmawaty (Universitas Hasanuddin, 2018)
This research aims to reveal the use of address terms in English and Selayarese based on situation and context and to understand the aspects that influenced the use of address terms in English and Selayarese. This study was analyzed through descriptive qualitative approach. The English data were taken from some conversational events in the movies while the Selayarese data were taken from the participant observation, depth interview, and field notes. The data requirement is focused on the address terms performed by English (American) and Selayarese community. The results of this research indicate some kinds of address terms occupied in both languages namely: 1) pronouns, 2) kinship terms, 3) title and professional terms, 4) religious terms, 5) nobility terms, 6) terms of endearments. The difference from both languages appeared in which the nobility terms and teknonyms was not accommodated in English data. Another difference is Selayarese use certain address terms to call cousin and nephew or niece. Beside that there are also some similarities from both languages in which they use first name to call their mother, father, grandfather and grandmother and both languages applied endearments to address someone. It was also found from the data that there are some aspects that influenced the use of address terms in English and Selayarese, namely: 1) age difference, 2) social situation, consisting formal and non formal situation, 3) social status, consisting achieved and ascribed status, 4) social distance or degree of intimacy.